Atypical manifestations of acute hepatitis in adolescent age group: Mandatory to rule out Wilson’s disease - Najmuddin, Fehmida; Lahiri, Keya Rani; Sude, Anand; Bansal, Anshita; Reddy, Manisha; Wadhawan, Pallavi (Indian Journal of Case Reports, 2020)
Pediatric presentation of hepatitis A infection is usually anicteric, self-limiting with non-tender hepatomegaly and associated symptoms of malaise, fever, vomiting, headache, and abdominal pain. We, hereby report the case of an 11-year-old female child who presented to our tertiary care hospital with an atypical manifestation of hepatitis A virus (HAV) in the form of firm tender hepatomegaly, deep colored jaundice, and pruritis. Initially, the age and presentation of the child prompted us to investigate on the lines of Wilson’s disease which was negative and the HAV immunoglobulin M titers came positive. The child was given symptomatic treatment following which her signs and symptoms gradually improved. With this case, we want to highlight the importance of ruling out Wilson’s disease in such cases and the atypical features associated with HAV infection in the pediatric age group.